Who's asking? Interviewer effects on unit non-response in the Household Finance and Consumption Survey - Nicolas Albacete; Pirmin Fessler; Peter Lindner (European Central Bank (ECB), 2021)
This study examines interviewer effects on household non-response in the three waves of the Household Finance and Consumption Survey (HFCS) in Austria. We exploit the rare opportunity to combine this wealth survey data, accompanied by a large set of paradata on all households including non-respondents, with two other sets of data, namely (i) an administrative dataset on income and (ii) a survey on interviewer characteristics. These characteristics include measures of the social background, income and wealth, and personality traits of the interviewers. Our multilevel benchmark model shows that the proportion of the variation in response behaviour that can be explained at the interviewer level has decreased from about one-third in the first wave of the HFCS to about 7% in the third wave. Using further specifications of our multilevel model we find that the following interviewer characteristics are positively related to household response: having a university degree, being married, being a homeowner and having a less open personality. At the same time, we find a highly significant negative relationship between survey participation and mean wage in the household's municipality
Keywords: C21; C83; Y80; 330; unit non-response; interviewer effects; interviewer survey; HFCS